Comprehensive analysis on investigating water-saving potentials of irrigated cotton in semi-arid area in China - Zhi, Xiaoyu; George-Jaeggli, Barbara; Han, Yingchun; Chen, Qiaomin; Zhang, Shijie; Feng, Lu; Lei, Yaping; Li, Xiaofei; Wang, Guoping; Wang, Zhanbiao; Xiong, Shiwu; Xin, Minghua; et al. (Agricultural water management, 2024)
Deficit irrigation is a common strategy to reduce water use and improve the sustainability of cotton production. However, the effects of water deficits on crop productivity and quality are subject to genotype by management by environmental interactions. This study investigated effects of water deficits and frequency of irrigation on cotton performance grown in semi-arid region, Xinjiang, the main cotton-growing area in China. Two field trials (2020 and 2021) with split experimental design, including main factors of three irrigation levels (moderate-deficit, mild-deficit and full-irrigation) and split factors of three irrigation frequencies (4, 8 and 12 days) were conducted. Results from two trials both showed little negative influence of irrigation levels on yield, and higher irrigation frequency improved yield under same irrigation level. Significant effects of irrigation levels on yield components were found in 2021, with a 22 % increase in boll number and an 18 % reduction in boll weight under moderate-deficit irrigation compared with those under full-irrigation. Interactions between irrigation levels and frequencies significantly affected harvest index (HI), showing that reduced irrigation might be beneficial for improving HI. However, decreased fibre length while increased fibre micronaire were found under deficit irrigation. A strong association between radiation use efficiency (RUE) and boll growth rate was observed, suggesting that RUE might be the driving force of yield formation. A tight correlation between both biomass and transpiration efficiency versus delta temperature between air and canopy (ΔTair-canopy) was observed, suggesting ΔTair-canopy could be used as an efficient tool to assess plant production under deficit irrigation. This study provided an improved understanding of the physiological basis of cotton yield formation and further identified a high-throughput and instantaneous method to monitor effects of deficit irrigation on crop productivity. •High irrigation frequency could be a promising alternative for water saving in semi-arid areas.•Deficit irrigation increased fibre micronaire and reduced length.•Reduced irrigation could stimulate dry matter to root at early stage and to boll at flowering stage.•Delta air to canopy temperature is a promising surrogate for biomass and transpiration efficiency in cotton.